2014
DOI: 10.1108/jsbed-10-2013-0152
|View full text |Cite
|
Sign up to set email alerts
|

Are growth-oriented SMEs more likely to adopt market and brand orientations?

Abstract: Purpose – The purpose of this paper is to examine how SMEs with varying growth intentions differ from each other with regard to market orientation and brand orientation. Both of these strategic orientations are seen to lead to enhanced market performance. Consequently, the authors investigate whether those small firms that regard growth as an important goal have adopted market or brand orientation. Design/methodology/approach – Responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…On the other hand, SMEs tend to regard brand building as something that is appropriate only for large companies (Merrilees, 2007). However, branding helps entrepreneurial small businesses to focus their efforts on those opportunities that have the greatest potential Industrial Marketing Management xxx (2015) xxx-xxx to contribute to firm performance (Merrilees, 2007) and it has been suggested that SMEs with higher levels of growth orientation are also more brand-oriented (Reijonen, Párdányi, Tuominen, Laukkanen, & Komppula, 2014). Therefore, brand orientation supports small firms in sharpening their strategies.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, SMEs tend to regard brand building as something that is appropriate only for large companies (Merrilees, 2007). However, branding helps entrepreneurial small businesses to focus their efforts on those opportunities that have the greatest potential Industrial Marketing Management xxx (2015) xxx-xxx to contribute to firm performance (Merrilees, 2007) and it has been suggested that SMEs with higher levels of growth orientation are also more brand-oriented (Reijonen, Párdányi, Tuominen, Laukkanen, & Komppula, 2014). Therefore, brand orientation supports small firms in sharpening their strategies.…”
Section: Introductionmentioning
confidence: 98%
“…When reviewing the academic studies in the literature, it is understood that different perspectives are used for the concepts of market orientation, brand orientation and firm performance. Narver, and Slater (1990), Reijonen et al (2014) have considered customer orientation, competitiveness, and coordination of departments to be one approach in interpreting market orientation. In summary, these studies are interpreted as being marketoriented, customer-oriented, and orientation towards the rivalry and cooperation between the units.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors have claimed for a long time that market orientation and brand orientation and firm performance should be linked Narver & Slater 1990;Kohli, Jaworski, and Kumar (1990) //dx.doi.org/10.15405/epsbs.2017.12.02.5 Corresponding Author: T. Sabri Erdil Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 52 resulting from consistency in marketing strategies (Hu et al 2012;Hirvonen, & Laukkanen 2014;Ramli, & Iskander, 2014;Reijonen et al 2014). …”
Section: Literature Reviewmentioning
confidence: 99%
“…It is true that marketing performance can be measured through many different aspects; brand orientation is one of these main aspects, which streams to brand performance and-as a result-to marketing performance in general. Reijonen et al (2014) [65] survey 492 SEMs to find the impact of growth intention on brand orientation, and they find that corporations with a high intention for growth are likely to become highly brandoriented. Another research establishes a significant relationship between brand orientation and customer relationship performance and that whenever brand orientation increases there will be an increase in customer relationship performance (Chovancova et al, 2015) [20].…”
Section: Brand Orientationmentioning
confidence: 99%